Bortezomib-Containing Regimen for Primary Treatment of Early Antibody-Mediated Cardiac Allograft Rejection: A Case Report. (June 2015) - Gazdic, Tomas; Svobodova, Eva; Kubanek, Milos; Kment, Martin; Pagacova, Libuse; Viklicky, Ondrej; Malek, Ivan; Kautzner, Josef
Evidence regarding the use of bortezomib-containing schemes in primary treatment of antibody-mediated rejection in heart transplant recipients is scarce. This case report presents the clinical experience with upstream use of bortezomib in primary treatment of early antibody-mediated rejection in an adult heart transplant recipient. Two cycles of bortezomib together with methylprednisolone, immunoadsorption, rituximab, and supplementary doses of intravenous immunoglobulin G reversed signs of heart failure, production of donor-specific antibodies, and findings of antibody-mediated rejection in biopsy. This treatment regimen was tolerated with only mild hematologic toxicity and proved to be successful during a 12-month follow-up. Primary treatment with a bortezomib-containing regimen appears to be a new therapeutic option for severe antibody-mediated rejection in heart transplant recipients. However, the efficacy and safety of this treatment need to be tested in prospective trials.